Chemical structure of steroidal saponin isolated from the leaves of Dracaena draco L. - Hung Duc Nguyen*; Tan Quang Tu; Mau Hoang Chu (Vietnam Journal of Science, Technology and Engineering, 2024)
Saponins are naturally occurring compounds ubiquitously present in various organisms, predominantly in plants. They are noted for forming colloidal solutions in water, which foam on shaking and precipitate cholesterol. Several in vitro and in vivo tests on mixtures and individual saponins have revealed a broad spectrum of biological and pharmacological activities, including cancer-related activity, antiphlogistic and antiallergic, immunomodulating, antihepatotoxic, antiviral, hypoglycemic, antifungal and molluscicidal activities. The Dracaena genus is renowned for an abundance of steroidal saponins utilized in treating digestive and hematological disorders. Previous studies on this genus revealed the presence of steroidal saponins, some of which showed cytotoxic activities against cultured tumor cells and interesting biological activities. This study procured steroidal saponin from the foliage of D. draco L. using various chromatographic techniques and 1D and 2D nuclear magnetic resonance (NMR) spectroscopic analysis. The structure was deduced as 26-O-β-D-glucopyranosyl-22-O-methylfurosta-5,25(27)-diene-1β,3β,22α,26- tetrol 1-O-{O-α-L-rhamnopyranosyl-(1→2)-α-L-arabinopyranosyl}; a compound previously isolated from the underground parts of Ruscus aculeatus in Japan. Future evaluation of the saponin’s biological activity is imperative to enhance chemotaxonomic data concerning the chemical composition and biological functionality of D. draco L. and, by extension, the Dracaena genus.